QOLP-13. RETROSPECTIVE REVIEW OF HOSPICE CARE UTILIZATION IN GLIOBLASTOMA PATIENTS IN A TERTIARY CARE CENTER. (12th November 2021) - Puri, Sushant; Heron, David; NIcholas, Martin; Huber, Michael; Tuite, Jason; Puri, Sushant
Abstract: BACKGROUND: Glioblastoma is a highly aggressive grade IV tumor of the brain. Standard of care is maximal safe resection followed by radiation therapy and chemotherapy. Despite optimal management, majority recur, and the median survival is 2-3 years. Hospice is a philosophy of care to alleviate end-of-life suffering, and it can also relieve caregiver fatigue. METHODS: This is a retrospective chart review in a tertiary care center. IRB approval was obtained from the Office for the Protection of Research Subjects. ICD-10 code for malignant gliomas C71.9 was used to query EMR at UIC from 2015-2020. Patients with primary glioblastoma that had their entire neuro-oncologic care at UIC were included in the data analysis. Patient's age < 18 years, unknown date of death, or those who transitioned to a different facility were excluded. Data included were demographic (including marital status as a proxy for social support), insurance, ethnicity, tumor characteristics, and treatments provided. End-of life quality measure assessed were (1)no chemotherapy < 2w, (2)hospice status < 7 days, (3)no hospital admission > 30 days (4)no ICU admission < 14 days. RESULTS: 48 patients with primary glioblastoma were identified and out of those, a total of 35 patients received entirety of neurooncological care at our center. Date of death was available for 13 patients. 9 patients had been referred to hospice and 4 were not. Demographic variables were similar except social support – patients referred to hospice were more likely to be married. End-of-life quality measures were met in all patients in hospice group (9/9) but only in half of those not referred to hospice (2/4). DISCUSSION: Social support has an impact on enrollment of hospice care. Including goals of care discussion earlier in the treatment would require a multi-disciplinary team with additional involvement of supportive care, nurses, and social workers.